(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to study the importance of applying lean accounting techniques and the tools and methods they include. The most important of these methods is the “value stream costing” technique and its impact on reducing and controlling costs, in addition to reducing production costs in general and reducing quality costs in particular. By reducing or eliminating waste and losses in both time and resources and meeting customer requirements. In order to achieve this goal, the researcher relied on applying lean accounting tools by obtaining data related to the station, in addition to the information obtained as a result of field experience in the station and being able to view the records of the station that is the research sample. From the above, the researcher reached several conclusions, the most important of which is that Al-Muthanna Power Station adopts traditional concepts of cost accounting and is far from the concepts of reduction and the tools it includes, through which production costs can be reduced in general and quality costs in particular, in addition to reducing costs, which is one of the most important The main components for achieving the goals and success of the economic unit, which is the customer who directs the unit towards production and marketing.